2004
DOI: 10.1038/sj.emboj.7600155
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial ARTS protein promotes apoptosis through targeting XIAP

Abstract: ARTS is an unusual septin-like mitochondrial protein that was originally shown to mediate TGF-beta-induced apoptosis. Recently, we found that ARTS is also important for cell killing by other pro-apoptotic factors, such as arabinoside, etoposide, staurosporine and Fas. In Drosophila, the IAP antagonists Reaper, Hid and Grim are essential for the induction of virtually all apoptotic cell death. We found that mutations in peanut, which encodes a Drosophila homologue of ARTS, can dominantly suppress cell killing b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
220
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(230 citation statements)
references
References 43 publications
7
220
0
3
Order By: Relevance
“…The increased expression of sept4 observed in the lateral SN may be associated with the higher attrition of dopaminergic neurones in this anatomical region. Sept4 has been ascribed a role in neuronal differentiation and axon guidance through the control of mitochondrial function [64] and importantly, causes caspase activation [21]. Interestingly, in cultured neuroblastoma and fibroblast cells, co-expression of sept4 and SNCA synergistically accelerated cell death induced by the proteasome inhibitor, lactacystin [27].…”
Section: Discussionmentioning
confidence: 99%
“…The increased expression of sept4 observed in the lateral SN may be associated with the higher attrition of dopaminergic neurones in this anatomical region. Sept4 has been ascribed a role in neuronal differentiation and axon guidance through the control of mitochondrial function [64] and importantly, causes caspase activation [21]. Interestingly, in cultured neuroblastoma and fibroblast cells, co-expression of sept4 and SNCA synergistically accelerated cell death induced by the proteasome inhibitor, lactacystin [27].…”
Section: Discussionmentioning
confidence: 99%
“…Independently, Larisch et al (2000) observed that what is now known as a SEPT4 transcript (and was previously named ARTS) could promote TGF betamediated apoptosis. It has been reported that the SEPT4 isoform encoded by this transcript binds to and can modulate the function of XIAP and thus promote apoptosis (Gottfried et al, 2004). Subsequent studies have suggested that the expression of this transcript (which is distinct from those reported by Tanaka et al) might function as a tumour suppressor since expression is lost in most cases of childhood ALL (Elhasid et al, 2004).…”
Section: Other Septins and Cancermentioning
confidence: 94%
“…21,22 Although these results could be interpreted to indicate that IAPs do not play a major role for caspase regulation in mammals, a more likely alternative is that their physiological role is masked by functional redundancy. If relatively short-lived organisms such as fruit flies protect themselves against unwanted death using multiple caspase inhibitors (see below; Figure 1), 6,[8][9][10][11][12][13][14][15][23][24][25][26][27][28][29][30][31][32][33][34][35] it would come as a great surprise if mammals would employ fewer safeguards to control caspase activity.…”
Section: Brakes On Death: Caspase Inhibition By Inhibitor Of Apoptosimentioning
confidence: 99%